Przestrzenne uwarunkowania funkcji szkoł. Wokół pojęcia przestrzeni jako kategorii pedagogiki stosowanej - Dylak, Stanisław; Skrzypczak, Józef (Wydawnictwo Naukowe UAM w Poznaniu, 1992)
The paper discusses the proposition of analysing of school's infrastructure and its theoretical foundation. The essential features of school's infrastructure are stated by a shape and organizational space of a school building. However, the school's infrastructure should be analysed on the base of incontrology i.e. philosophy of human meeting and on the base of sociology of big cities centers. To conclude the authors contained the set of the basic questions which should be answered; and the authors have proposed some procedures for searching.
The proposition of analysing of school's infrastructure and its theoretical foundation
Keywords: Infrastuktura szkolna; School’s infrastructure; Przestrzeń; Extent; Funkcje przestrzeni; Function of space; Szkoła ekologiczna; Ecological school; Ergononia; Ergonomics